2019
DOI: 10.24028/gzh.0203-3100.v41i4.2019.177363
|View full text |Cite
|
Sign up to set email alerts
|

Density heterogeneity of the Earth’s crust of the Black Sea megadepression and adjacent territories from three-dimensional gravity modelling. 1. Regional density distribution at different depths.

Abstract: Введение. Анализ ранее опубликованных работ по двух-и трехмерному плотностному моделированию земной коры Черного моря показал, что во всех построенных моделях используются одни и те же карты мощности разновозрастных осадочных отложений, приведенных, на

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Deep faults, including strike-slips, do not participate in the constructions. The differentiated nature of β-factors distribution in the EBSB correlates with the heterogeneous density at the Moho section and the basaltic type of the crust in the center of the subbasin [Makarenko et al, 2021].…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Deep faults, including strike-slips, do not participate in the constructions. The differentiated nature of β-factors distribution in the EBSB correlates with the heterogeneous density at the Moho section and the basaltic type of the crust in the center of the subbasin [Makarenko et al, 2021].…”
mentioning
confidence: 87%
“…In addition, as a continuation of the fault in the Western and Central Pontides, it should cross the Western subbasin in the central part. Our comprehensive studies on the fault tectonics of the crystalline crust [Rusakov, Pashkevich, 2017] showed that such a meridional strike-slip does not manifest itself either in potential fields or in the 3D density model of the crystalline crust [Makarenko et al, 2021]. Spadini G. et al [1996] put forward an innovative idea that pre-rift contrast lithospheric structure controls Black Sea formation.…”
mentioning
confidence: 97%
See 3 more Smart Citations